Why borrowers pay premiums to larger lenders: Empirical evidence from sovereign syndicated loans - Issam Hallak (Goethe University Frankfurt, Center for Financial Studies (CFS), 2002)
All other terms being equal (e.g. seniority), syndicated loan contracts provide larger lending compensations (in percentage points) to institutions funding larger amounts. This paper explores empirically the motivation for such a price design on a sample of sovereign syndicated loans in the period 1990-1997. I find strong evidence that a larger premium is associated with higher renegotiation probability and information asymmetries. It hardly has any impact on the number of lenders though. This is consistent with the hypothesis that larger lenders act as main lenders, namely help reduce information asymmetries and provide services in situations of liquidity shortage. This constitutes new evidence of the existence of compensations for such unique services. Moreover, larger payment discrepancies are also associated with larger syndicated loan amounts. This provides further new evidence that larger borrowers bear additional borrowing costs.
urn:nbn:de:hebis:30-9921
Keywords: F34; G21; G33; 330; Relationship Lending; Number of Lenders; Syndicated Loans; Sovereign Debt